2013
DOI: 10.1371/journal.pone.0055121
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic and Molecular Epidemiological Studies Reveal Evidence of Multiple Past Recombination Events between Infectious Laryngotracheitis Viruses

Abstract: In contrast to the RNA viruses, the genome of large DNA viruses such as herpesviruses have been considered to be relatively stable. Intra-specific recombination has been proposed as an important, but underestimated, driving force in herpesvirus evolution. Recently, two distinct field strains of infectious laryngotracheitis virus (ILTV) have been shown to have arisen from independent recombination events between different commercial ILTV vaccines. In this study we sequenced the genomes of additional ILTV strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
51
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(55 citation statements)
references
References 41 publications
4
51
0
Order By: Relevance
“…High‐throughput genome sequencing has provided evidence of recombination between strains in other herpesviruses, namely HSV‐2, VZV, Marek's disease virus, HSV‐1, pseudorabies virus, human cytomegalovirus and infectious laryngotracheitis virus (Hughes & Rivailler, 2007; Kolb, Larsen, Cuellar, & Brandt, 2015; Lee et al., 2013; Norberg et al., 2011, 2015; Sijmons et al., 2015; Szpara et al., 2014; Szpara, Tafuri, et al., 2011; Zell et al., 2012). In the present study, network analysis suggested that recombination has also occurred between EHV‐1 strains.…”
Section: Discussionmentioning
confidence: 99%
“…High‐throughput genome sequencing has provided evidence of recombination between strains in other herpesviruses, namely HSV‐2, VZV, Marek's disease virus, HSV‐1, pseudorabies virus, human cytomegalovirus and infectious laryngotracheitis virus (Hughes & Rivailler, 2007; Kolb, Larsen, Cuellar, & Brandt, 2015; Lee et al., 2013; Norberg et al., 2011, 2015; Sijmons et al., 2015; Szpara et al., 2014; Szpara, Tafuri, et al., 2011; Zell et al., 2012). In the present study, network analysis suggested that recombination has also occurred between EHV‐1 strains.…”
Section: Discussionmentioning
confidence: 99%
“…Even with the unequal numbers of isolates from the different geographical regions, higher rates of recombination were detected within Australian isolates. Vaccine strains, including the Serva, A20, and SA2 strains, were frequently involved in recombination events among the Australian isolates (2,34). In contrast, vaccine strains did not typically feature in the recombination events detected in the U.S. strains, although the Laryngovac strain was identified as a minor parent in one recombination event and some field strains, such as 1874c5 and J2, were involved in recombination events (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…In many alphaherpesviruses, recombination is increasingly being recognized as an important mechanism that plays a major role in evolution of viruses with an otherwise stable DNA genome that have low rates of nucleotide substitution (Lee et al, 2013(Lee et al, , 2012Thiry et al, 2005). Recent advances in high-throughput sequencing of complete viral genomes have allowed natural (field) recombination to be studied in a number of different alphaherpesviruses affecting animals and humans, including herpes simplex virus 1 (HSV-1), varicella-zoster virus (VZV) and infectious laryngotracheitis virus (ILTV) (Kolb et al, 2013;Lee et al, 2013;Norberg et al, 2015Norberg et al, , 2006Peters et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in high-throughput sequencing of complete viral genomes have allowed natural (field) recombination to be studied in a number of different alphaherpesviruses affecting animals and humans, including herpes simplex virus 1 (HSV-1), varicella-zoster virus (VZV) and infectious laryngotracheitis virus (ILTV) (Kolb et al, 2013;Lee et al, 2013;Norberg et al, 2015Norberg et al, , 2006Peters et al, 2006). Such studies provide insights into virus evolution and also allow the risk of recombination to be assessed in the context of attenuated vaccine use.…”
Section: Introductionmentioning
confidence: 99%